Spectroscopic characterization of the maltene fraction of Nigerian bitumen for potential health-risk assessment. Issue 16 (17th August 2016) - Adebiyi, F. M.; Ogunlaja, O. T.; Santoro, A.; Thoss, V.
ABSTRACT: This study was carried out on maltene fraction of Nigerian bitumen to infer the environmental and health implications of its uses and also to characterize the fossil fuel. Bitumen was extracted from the oil sands obtained from six locations in Southwestern Nigeria using toluene via Soxhlet extraction and then deasphalted using n-pentane. The organic components of the maltenes were investigated using Fourier transform infrared spectroscopy, while the elemental content was determined using inductively coupled plasma-optical emission spectrometry (ICP-OES) and the radioactivity levels were measured using a sodium iodide (NaI)-based Gamma Spectrometry Detector System. The IR spectra of the maltene indicated the presence of various organics and heteroatoms, corroborating the fact that maltene is composed of high molecular weight polycyclic constituents comprising nitrogen, sulfur, and oxygen heteroatoms. The result of the elemental concentrations revealed that sulfur with the mean value of 2.155 μg/g comparatively has the highest concentration in the samples, followed by Fe (1.25μg/g), while Mn has the least value (0.075) μg/g. The values of the analyzed elements were comparatively lower in the maltene fraction than in the bitumen and higher molecular weight fractions of Nigerian bitumen, but higher than the maltene fraction of Nigerian crude oil (except Cr and Ni). The result of the cross-plot analysis between maltene and bitumen using their elemental mean concentrations as variables indicated significant strong and positive correlation (R 2 = 0.81) between them, indicating very strong inter-element and geochemical relationships between them. The elements showed close clustering, indicating similar sources or similar chemical affinity. The average activity concentrations of 238 U, 232 Th, and 40 K determined with a view to ascertaining the radiological health consequences associated with the burning of this maltene fraction were 1.66 ± 1.07, 0.72 ± 0.49, and 15.93 ± 3.37 Bqkg −1, respectively. These values are below the standard values in radiation protection. The radiological health consequences associated with the burning of maltene fraction of Nigerian bitumen were insignificant with no radiological hazard to the general public, but long exposure may pose an intrinsic health hazard.